The Controversy Between Universal and Particular Human Rights in The Context of Indonesia - Indah Harlina; Jum Anggariani; Tetti Samosir; Utji Sri Wulan Wuryandari; Ahmad Dahlan (Khazanah Hukum, 2026)
This study examines the dialectic between the concepts of universal and particular human rights in the Indonesian context. Through an analysis of legal documents, historical treatises, and constitutional practices, the study reveals how Indonesia developed a "contextual universalism" approach that harmonizes universal human rights values with national socio-cultural particularities. The study shows that the tension between the universality and particularity of human rights has been an inherent part of Indonesian human rights discourse since the 1957-1959 Constituent Assembly debates, long before the reform era. Islam and local culture have a significant influence in shaping Indonesia's particular conception of human rights, with Muslim scholars and mainstream Islamic organizations contributing to the reconciliation of universal human rights principles with Islamic values and local wisdom. The study identifies five main strategies used by Indonesia in harmonizing universal and particular human rights: the margin of national appreciation, cultural translation, a dialogical approach, mainstreaming human rights in public policy, and developing contextual human rights conflict resolution mechanisms. This research has important theoretical implications, challenging the rigid dichotomy of universalism versus relativism, strengthening the argument about multiple modernities in human rights discourse, and underlining the importance of vernacularization. In practice, Indonesia faces challenges in harmonizing regulations and strengthening human rights culture, but it also has opportunities to develop global human rights diplomacy and a transformative human rights model rooted in the values of Pancasila and Indonesian constitutionalism.